Southwest Research-Extension Center, Field Day 2013 (Kansas Agricultural Experiment Station Research Reports, 2013)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: crops; tillage; soil fertility; weed science; SRP1088; 2013